PENGARUH PRODUK, HARGA, PROMOSI, DAN SALURAN DISTRIBUSI TERHADAP MINAT BELI KONSUMEN PADA PRODUK SHAMPO PT. L’OREAL (Survei pada konsumen produk shampo L’Oreal di Kota Pontianak) - admin, M. DIMAS DIANQADARI B11110124 (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of the product, price, promotion, and distribution channels to consumers to buy. The study was designed as a descriptive study. The population of this study were men and women who have been or have not used the L'Oreal shampoo products. This research uses accidental sampling with a sample size of 100 people. The analysis technique used is multiple linear analysis using SPSS version 17.0. Based on tests conducted feasibility of this model shows a model in this study deserves to be tested. The results of the analysis show that the variable pricing, and distribution channels do not have a significant influence on the variable consumer purchase interest in L'Oreal shampoo products. As for the variable products and promotions have a significant influence on the variable consumer purchase interest in L'Oreal shampoo products. Keywords: Product, Price, Promotion, Distribution Channels, Buying Interest